Walking across evidence and sustainability of public health policies -do we need a new journal? (Italian Journal of Public Health, 2012)
Despite the title, this is not an announcement of a new journal. With the first issue of 2013, the Italian Journal of Public Health will change its name, after ten years, and Epidemiology, Biostatistics, and Public Health (EBPH) is ready to pick up the baton.With the launch of Epidemiology, Biostatistics, and Public Health, the Italian Journal of Public Health incorporates another existing journal: Biomedical Statistics and Clinical Epidemiology.The two main reasons for this change lie both in the title of the new journal. The first one refers to public health as the key of our scientific and editorial policy.EBPH aims to be a support for the International scientific community in its efforts to reduce the negative impact on public health of the current economic situation, and most specifically to provide scientific evidence to serve as a basis for the difficult economic and financial choices now required in any Public Health policy.